TEMPERATURE EFFECT ON REFRACTOMETRIC DOUBLE RING RESONATOR - Azam Mohamad; M. S. Aziz; Mahdi Bahadoran; Kashif Chaudary; M. Arif Jalil; Jalil Ali; Preecha P. Yupapin (My University, 2015)
The effect of temperature on double ring resonator (DRR) glucose sensing is investigate theoretically and proposed. Different from other optical resonator, the pulse laser is used as an input source and the vertical DRR configuration is used. The concept for pulse propagation is based on the split-step Fourier method. Result shows that the detection of glucose is measured by optical losses and the losses at 26oC are 1.86 dB at through and 0.93 dB at drop port, respectively. The performance of glucose sensing on DRR is degraded by temperature. Effect of temperature creates more losses which results total loss of 2.01 dB at through and 1 dB at drop port when temperature increase by 1oC.
Keywords: Port (circuit theory); Photonic and Optical Devices